2D mesoscale model for concrete based on the use of interface element with a high aspect ratio. (September 2016) - Rodrigues, Eduardo A.; Manzoli, Osvaldo L.; Bitencourt Jr., Luís A.G.; Bittencourt, Túlio N.
Abstract: The mesostructure of concrete plays a very important role in the process of initiation and propagation of cracks. Microcracks tend to start in the Interfacial Transition Zone (ITZ) and propagate toward the mortar matrix until a macrocrack formation. Seeking to better understand the influence of the concrete mesoscopic structure, translated macroscopically in the form of loss of stiffness and energy dissipation, this work proposes a 2D mesoscale model in which the concrete is modeled as a heterogeneous three-phase material composed of coarse aggregates, mortar matrix and ITZ. The coarse aggregates are generated from a grading curve and placed into the mortar matrix randomly. Interface solid finite elements with a high aspect ratio are used to represent the ITZ and the crack process based on a mesh fragmentation technique. These interface elements present the same kinematics as the Continuum Strong Discontinuity Approach (CSDA), which allows the use of a continuum constitutive relation to describe their behavior. Thus, an appropriate continuum tension damage model is adopted to describe the complex nonlinear behavior of concrete due to the crack phenomenon. Initially, the proposed mesoscale approach is applied in uniaxial tensile tests to study the influence of the size, volume and distribution of the coarse aggregates within the mortar matrix. Then, three-point bending beams are simulated in mesoscale and the results compared with the experimental ones. The results showed that the proposed 2D mesoscale model presents the same kinds of characteristics that real 3D concrete shows, considering the effects of the mesostructure constituents.